PRAGMATIC FEATURES OF COMPLEX CONSTRUCTIONS (Ustozlar uchun, 2025)
Complex sentence constructions—consisting of coordination, subordination, and conditional structures—are fundamental units of natural language communication. While syntactic and semantic aspects of such constructions have been studied extensively, their pragmatic functions remain underexplored. This paper investigates how complex constructions operate pragmatically in spoken and written English discourse. Drawing on authentic data from two major corpora, the study analyzes the use of complex sentences in relation to politeness, implicature, coherence, and information management. The results show that complex constructions are pragmatically multifunctional: they structure discourse, support indirectness, frame context, and convey speaker attitude. These findings have implications for discourse analysis, language education, and cross-cultural pragmatics.